THE BENEFITS OF RECREATION FOR CHILDREN: THE HOSPITAL PLAYROOM IN GAME (Fiep Bulletin - online, 2014)
This article aims to map the professional as well as recreational activities in a hospital located in the southern state of Rio Grande do Sul, based on the Federal Law 11,104 of 2005, which provides for the existence of a playroom in hospitals. The methodology used to collect as much as for the data analysis was the Discursive Textual Analysis, drawing on numerous sources of evidence such as document analysis, interviews and observations. From the data collection, it was revealed that the hospital analyzed school relies upon Federal believing that the use of recreation in the treatment of hospitalized people has contributed in improving health in pursuit of quality of life, such as a forms view the various ways to improve the psychological health of the sick child.
Keywords: Recreation; Childhood; University Hospital.